PENGARUH MOTIVASI, BUDAYA PERUSAHAAN DAN STRES KERJA TERHADAP KINERJA PEGAWAI PT. TELKOM SEMARANG - Adisti Nurul Aulia; Agus Hermani; Bulan Prabawani (Universitas Diponegoro, 2015)
Telkom Semarang is a branch from Indonesia State Owned Enterprise, Telkom Indonesia, which provides the telecomunnication service at their best. Telkom Semarang supports any means to enhance the job performance, especially by the employee performance. To manage the employee’s performance, Telkom Semarang use a special assesment system named Competency Based Human Resouce Management (CBHRM) which evaluates job performance within two assesments, competency and achievement based. From 2012-2015, most of the employees have worked above the standard, however, the number of employees who reached this achievement were decline year by year. In addition, there was a contrast between the incline of the employees competencies and the decline of the achievements.The objectives of this research is to examine the influence of motivation, corporate culture and work stress with employee’s performance of Telkom Semarang. The type of this research is an explanative research. The sampling method used was incidental sampling (non-probability sampling). The total sampling of this research was 74 employees of Telkom Semarang. Measurement scales used was modified Likert (1-6). Quantitative analysis used were validity test, realibility test, crosstab, the coefficient of corelation, linear and multiple regression, the coefficient of determination, and significant test (t and F test) using SPSS 15.0.Based on the analysis, it was found that in partial, the variable of motivation contributes 17,6% of the employees performance, while corporate culture contribution is 55,7% and work stress contribution is 67,4%. Simultaneously the variable of motivation, corporate culture and work sress contribute 69,7% of the employees performance.Based on the results, the researcher suggest that the company should improve the rewarding for the employees outside from their works, giving a comprehensive leadership training as well as the job training for the employees of Telkom Semarang.